Strategi Komunikasi Penyuluh Agama Islam dalam Program Pembinaan Keluarga Sakinah untuk Menekan Tren Perceraian di Kota Bandung - Yuni Putri Lestari; Muhammad Bangkit Putra Trisani; Hani Hadiati Pujawardani (IAIN Madura, 2024)
This research was motivated by the problem of increasing divorce rates. The purpose of this study is to identify communication strategies used by religious counselors in the Sakinah family development program to emphasize divorce trends in the city of Bandung. This research is located at the Ministry of Religious Affairs of Bandung City, with a qualitative approach and descriptive method. The instruments used in this study were interview guidelines, observation guidelines, and documentation studies. The steps for implementing the research are collecting interview data from resource persons who are then processed, the results of observational observations in the field, and collecting available documents. The results of this study show that the communication strategies applied by Islamic extension workers in the city of Bandung in the Sakinah family development program include; making a work program plan and design modules of the Bride and Groom Course (Suscatin) and counseling. Giving lectures, sermons, and seminars in mosques, ta'lim assemblies, and community activities. The obstacles of Islamic extension workers in implementing communication strategies for Islamic extension workers to reduce divorce rates in the city of Bandung, namely: differences in the level of education and literacy of program participants, accessibility and mobility, lack of resources such as funds and facilities